On quadruple integral equations involving trigonometric kernels - B. D. Aggarwala (International Journal of Mathematics and Mathematical Sciences)
A general technique is developed for the solution of quadruple integral equations involving trigonometric kernels. Four such sets are solved explicitly. Application is made to the problem of three-collinear cracks in linear plane elasticity.